Synthesis of nanostructured lithium zirconium phosphate
Patent Information
- Application Number
- JP2023513623
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-07
- Filing Date
- 2021-03-19
- Publication Date
- 2025-02-20
- Estimated Expiration
- 2041-03-19
Smart Images

Figure 0007634084000002 
Figure 0007634084000003 
Figure 0007634084000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a process for the preparation of lithium zirconium phosphate by flame spray pyrolysis, to the lithium zirconium phosphate obtainable by this process, and to its use in lithium ion batteries. [Background technology]
[0002] Secondary lithium-ion batteries are one of the most important battery types in use today. They usually consist of a negative electrode made of a carbon material or a lithium metal alloy, a positive electrode made of a lithium metal oxide, an electrolyte consisting of a lithium salt dissolved in an organic solvent, and a separator that allows lithium ions to pass between the positive and negative electrodes during charging and discharging.
[0003] In an attempt to develop secondary batteries with improved intrinsic safety and energy density, the use of solid electrolytes instead of liquid electrolytes has made considerable progress in recent years. Among such systems, secondary lithium batteries with electrodes made of lithium metal or lithium metal alloys offer high energy density and are considered to be particularly suitable. Such all-solid-state secondary lithium-ion batteries require good ionic conductivity at the interface between the electrode active material and the electrolyte to obtain the required load characteristics. This high ionic conductivity can be achieved by coating the surface of the active electrode material with some lithium-containing compounds, such as LiTi2(PO4)3, as described in Japanese Patent Publication No. 4982866.
[0004] H. Xiea et al., in Journal of Power Sources 2011, vol. 196, pp. 7760-7762, reported the production of Li by solid-state reactions of ZrO with LiCO, NHHPO, and CaCO. 1.2 Zr 1.9 Ca 0.1The preparation of lithium zirconium phosphate (PO4)3 is described. The Li-ion conductivity of this lithium zirconium phosphate was measured using Li-ion batteries as a solid Li-ion separator in test cells. 1.3 Ti 1.7 Al 0.3 It was found to be comparable to (PO4)3.
[0005] Therefore, lithium zirconium phosphate is a promising candidate for Li-ion conducting materials to be used in lithium-ion batteries, especially all-solid-state batteries.
[0006] Y. Li et al., in PNAS, 2016, vol. 113(47), pp. 13313-13317, describe the preparation of rhombohedral LiZr2(PO4)3 by the solid-state reaction of (NH4)2HPO4 with Li2CO3 and zirconium acetate, and its use as a solid electrolyte in all-solid-state Li / LiFePO4 lithium-ion batteries.
[0007] I. Hanghofer et al., in Dalton Trans, 2019, vol. 48, pp. 9376-9387, report the synthesis of rhombohedral Ca-stabilized Li2CO3 by solid-state reactions of Li2CO3, (NH4)2HPO4, and CaCO3 with either ZrO2 or zirconium acetate, suitable as solid electrolytes for use in all-solid-state lithium-ion batteries. 1.4 Ca 0.2 Zr 1.8 The preparation of (PO4)3 is described.
[0008] Lithium zirconium phosphates prepared by solid-state synthesis typically have relatively high material density and low BET surface area, which makes such materials well suited for use as the core material of solid electrolytes in, for example, lithium-ion batteries.
[0009] However, if such compounds are envisaged to be used as additives that can be well distributed within a core material or on its surface, their smaller particle size, lower material density and higher BET surface area are crucial. [Prior art documents] [Non-patent literature]
[0010] [Non-Patent Document 1] Journal of Power Sources 2011, vol. 196, pp. 7760-7762 (H. Xiea et al.) [Non-Patent Document 2] PNAS, 2016, vol. 113(47), pp. 13313-13317 (Y. Li et al.) [Non-Patent Document 3] Dalton Trans, 2019, vol. 48, pp. 9376-9387 (I. Hanghofer et al.) Summary of the Invention [Problem to be solved by the invention]
[0011] The problem addressed by the present invention is to provide an improved process for the industrial production of crystalline lithium zirconium phosphate that can be used in lithium ion batteries, in particular as a coating or doping material for electrodes, especially negative electrodes, of lithium ion batteries, and as an additive to the electrolyte of lithium ion batteries.
[0012] Specifically, the method should provide lithium zirconium phosphate particles having a relatively small particle size, high BET surface area and low tamping density. Spray pyrolysis is a known method for producing a variety of metal oxides and certain metal salts.
[0013] In spray pyrolysis, metal compounds in the form of fine droplets are introduced into a high temperature zone where they are oxidized and / or hydrolyzed to give the corresponding metal oxides or salts. A special form of this process is that of flame spray pyrolysis, in which the droplets are fed into a flame formed by ignition of a fuel gas and an oxygen-containing gas.
[0014] US2013 / 0316233 generally discloses a method for producing a particle mixture suitable for use as a positive electrode active material for lithium-ion batteries, comprising feeding an aerosol formed from a solution containing a lithium source, a transition metal source, and a phosphorus source into a flame together with a combustion-supporting gas and a combustible gas. The transition metal can be selected from Fe, Mn, Ti, Cr, V, Ni, Co, Cu, Zn, Al, Ge, Zr, Mo, W, and the phosphorus source can be selected from phosphoric acid, ammonium phosphate, sodium phosphate, and ferrous phosphate. The specific examples in this patent application only show the preparation of lithium iron phosphate. The synthesis of lithium zirconium phosphate is not disclosed in US2013 / 0316233. Successful synthesis of this compound based on the general disclosure of US2013 / 0316233 requires laborious selection of appropriate lithium source, metal source, phosphorus source, solvent, and process conditions. Even so, it is not at all clear that this method will result in lithium zirconium phosphate with high BET surface area and low material density.
[0015] In the course of extensive experimentation, it was surprisingly found that lithium zirconium mixed phosphates having the desired particle properties can in fact be directly prepared by flame spray pyrolysis. However, the use of a specific combination of metal precursor, phosphorus precursor and solvent in the method of the present invention was found to be crucial to obtain particles having the desired properties according to the present invention. [Means for solving the problem]
[0016] Lithium Zirconium Phosphate The present invention relates to a compound of the general formula Li a Zr b M c (PO4) d wherein M is at least one metal different from Li and Zr, 0.5≦a≦5.0, 0.5≦b≦5.0, 0≦c≦5, 1≦d≦5, Lithium zirconium phosphate is in the form of aggregated primary particles, 5m 2 / g~100m 2 BET surface area in g / g, d as determined by static light scattering (SLS) 50 = numerical mean particle size between 0.03 μm and 2 μm, and It is characterized by having a tamping density of 20 g / L to 200 g / L.
[0017] The lithium zirconium phosphate of the present invention can be obtained by the process of the present invention described below.
[0018] The lithium zirconium phosphate of the present invention has the general formula Li a Zr b M c (PO4) d In the formula (I), M can be one or several elements selected from the group consisting of Na, K, Be, Mg, Ca, Sr, Ba, Zn, Co, Ni, Cu, Mn, B, Al, Ga, In, Fe, Sc, Y, La, Ti, Zr, Hf, Ce, Si, Ge, Sn, Pb, V, Nb, Ta, Mo, W, and preferably M=Ca.
[0019] The composition of the lithium zirconium phosphate of the present invention is preferably of the formula Li 0.8-1.5 Zr 1.5-2.5 M 0-0.5 (PO4) 2.5-3.5 , more preferably Li 1.0-1.3 Zr 1.8-2.2 M 0-0.3 (PO4) 2.8-3.2 is equivalent to.
[0020] The lithium zirconium phosphate of the present invention is 5m 2 / g~100m 2 / g, preferably 7m 2 / g~80m 2 / g, more preferably 15 to 60m 2 / g BET surface area.
[0021] The BET surface area can be determined according to DIN 9277:2014 by nitrogen adsorption according to the Brunauer-Emmett-Teller procedure. The lithium zirconium phosphate of the present invention is typically in the form of agglomerated primary particles having a numerical mean diameter of the primary particles of 1 to 100 nm, preferably 3 to 70 nm, more preferably 5 to 50 nm, as determined by transmission electron microscopy (TEM), which may be determined by calculating the average size of at least 500 particles analysed by TEM.
[0022] d in agglomerated form and possibly in the form of agglomerates 50 The numerical mean diameter of the lithium zirconium phosphate in is about 0.03 μm to 2 μm, more preferably 0.04 μm to 1 μm, and even more preferably 0.05 μm to 0.5 μm, as determined by static light scattering (SLS) after 300 seconds of sonication at 25° C. of a mixture consisting of 5 wt. % of the particles and 95 wt. % of a 0.5 g / L aqueous solution of sodium pyrophosphate.
[0023] Agglomerates and agglomerates can be broken down, for example, by grinding or sonicating the particles, resulting in particles having smaller particle sizes and narrower particle size distribution.
[0024] The lithium zirconium phosphate according to the present invention has a tamping density of 20 g / L to 200 g / L, preferably 25 g / L to 150 g / L, even more preferably 30 g / L to 100 g / L, even more preferably 40 g / L to 80 g / L.
[0025] The tamped density of powdery or coarse granular materials can be determined according to DIN ISO 787-11:1995 "General test methods for pigments and extenders - Part 11: Determination of tamped volume and apparent density after tamping", which involves measuring the apparent density of the bed after stirring and tamping.
[0026] Method for producing lithium zirconium phosphate
[0027] The present invention further provides a method for producing the lithium zirconium phosphate of the present invention by flame spray pyrolysis, comprising: At least one solution of metal precursors, lithium and zirconium carboxylates, each of which contains from 5 to 20 carbon atoms, -organophosphates, - a solvent containing less than 10% by weight of water; It is subjected to flame spray pyrolysis.
[0028] During the flame spray pyrolysis process of the present invention, a solution of metal compounds (metal precursors) and a phosphorus source in the form of fine droplets is typically introduced into a flame formed by ignition of a fuel gas and an oxygen-containing gas, and the metal precursors used are oxidized and / or hydrolyzed together with the phosphorus source to give the corresponding lithium zirconium phosphate.
[0029] The reaction initially forms highly dispersed, coarsely spherical primary particles, which in the further course of the reaction coalesce to form agglomerates. The agglomerates can then accumulate into agglomerates. In contrast to agglomerates, which in principle can be relatively easily separated into agglomerates by the introduction of energy, the agglomerates can only be further broken down, if at all, by the intensive introduction of energy.
[0030] The resulting aggregate compound can be referred to as "fumed" or "pyrogenically produced" lithium zirconium phosphate.
[0031] The flame spray pyrolysis process is generally described in WO2015173114 and elsewhere.
[0032] The flame spray pyrolysis process of the present invention preferably comprises the following steps: a) atomizing a solution of a metal precursor to obtain an aerosol by an atomizer gas; b) reacting the aerosol with a flame obtained by igniting a mixture of a fuel gas and an oxygen-containing gas in a reaction space of a reactor to obtain a reaction flow; c) cooling the reaction stream d) Then, removing the solid lithium zirconium phosphate from the reaction stream. Examples of fuel gases are hydrogen, methane, ethane, natural gas and / or carbon monoxide. It is particularly preferred to use hydrogen. Fuel gases are particularly used in embodiments where high crystallinity of the produced lithium zirconium phosphate is desired.
[0033] The oxygen-containing gas is typically air or oxygen-enriched air. Oxygen-containing gases are particularly used in embodiments where, for example, a high BET surface area of the lithium zirconium phosphate produced is desired. The total amount of oxygen is typically selected to be at least sufficient for complete conversion of the fuel gas and metal precursor.
[0034] To obtain an aerosol, the vaporized solution containing the metal precursors can be mixed with an atomizer gas, such as nitrogen, air, and / or other gases. The fine droplets of the resulting aerosol preferably have an average droplet size of 1-120 μm, particularly preferably 30-100 μm. The droplets are typically generated using a single or multiple material nozzle. The solution may be heated to increase the solubility of the metal precursors and to obtain a suitable viscosity for atomization of the solution.
[0035] The metal precursors used in the method of the present invention comprise at least one lithium carboxylate and at least one zirconium carboxylate, each containing from 5 to 20 carbon atoms. The lithium and zirconium carboxylates used in the process according to the invention may, independently of one another, be linear, branched or cyclic lithium and / or zirconium pentanoates (C5), hexanoates (C6), heptanoates (C7), octanoates (C8), nonanoates (C9), decanoates (D10), undecanoates (C11), dodecanoates (C12), tridecanoates (C13), tetradecanoates (C14), pentadecanoates (C15), hexadecanoates (C16), heptadecanoates (C17), octadecanoates (C18), nonadecanoates (C19), icosanoates (C20), as well as mixtures thereof.
[0036] Most preferably, zirconium 2-ethylhexanoate (C8) and lithium neodecanoate (C10) are used.
[0037] The metal precursors used may contain carboxylates or other salts of metals other than lithium and zirconium metals.
[0038] Besides the lithium and zirconium metal precursors, they may be inorganic metal compounds such as nitrates, carbonates, chlorides, bromides, or other organometallic compounds such as alkoxides, e.g., ethoxides, n-propoxides, isopropoxides, n-butoxides and / or tert-butoxides.
[0039] The term "organophosphate" in the context of the present invention relates to any compound having at least one group (R) containing at least one carbon atom linked via an oxygen atom to the phosphorus atom of the unit P(=O), such as a compound of the general formula (RO)P(=O) or (RO)(P(=O))2, where R is a group containing at least one carbon atom, such as methyl or ethyl.
[0040] The organophosphates used in the process of the present invention are preferably selected from esters of phosphonic acid (H3PO3), orthophosphoric acid (H3PO4), metaphosphoric acid (HPO3), pyrophosphoric acid (H4P2O7), polyphosphoric acid, and mixtures thereof.
[0041] The organophosphates may be selected from alkyl esters such as methyl, ethyl, propyl, butyl, hexyl, etc., aryl esters such as phenyl, mixed alkyl / aryl esters, and mixtures thereof.
[0042] The organophosphates are preferably esters having groups containing from 1 to 10 carbon atoms, most preferably alkyl groups containing from 1 to 10 carbon atoms.
[0043] The use of an organic phosphate as the phosphorus source has surprisingly been found to be key to obtaining small particles of lithium zirconium phosphate having high BET surface area and low tamping density.
[0044] The solvent mixture used in the process of the present invention may be selected from the group consisting of linear or cyclic, saturated or unsaturated, aliphatic or aromatic hydrocarbons, esters of carboxylic acids, ethers, alcohols, carboxylic acids, and mixtures thereof.
[0045] The solvent mixture used in the present invention contains less than 10% water by weight, preferably less than 5% water by weight, more preferably less than 3% water by weight, even more preferably less than 2% water by weight, and even more preferably less than 1% water by weight.
[0046] The low water content prevents the undesirable hydrolysis of zirconium carboxylates in the metal precursor solution.
[0047] The total metal content in the solution of metal precursors is preferably between 1% and 30% by weight, more preferably between 2% and 20% by weight, even more preferably between 3% and 15% by weight. Under "total metal content" is understood the total weight percentage of all metals contained in the metal precursors in the spent solution of metal precursors.
[0048] The solvent mixture used in the method of the present invention may further comprise a chelating agent, i.e., a compound capable of forming two or more coordinate bonds with metal ions. Examples of such chelating agents are, for example, diamines such as ethylenediamine, ethylenediaminetetraacetic acid (EDTA), and 1,3-dicarbonyl compounds such as acetylacetone and alkyl acetylacetates. As such a chelating agent, it is most preferred to use acetylacetone.
[0049] In the presence of such chelating agents, it has been observed that some metal precursors, such as zirconium compounds, exhibit better solubility and no precipitation after relatively long storage times.
[0050] The use of a special combination of metal precursor, phosphorus source and solvent in the method of the present invention ensures good solubility of all precursors and makes it possible to achieve the desired particle properties of the resulting lithium zirconium phosphate, such as small particle size, high BET surface area and low tamping density.
[0051] The method of the present invention may further include a step of heat treating the lithium zirconium phosphate produced by flame spray pyrolysis. This further heat treatment is preferably carried out at a temperature between 600°C and 1300°C, more preferably between 650°C and 1250°C, even more preferably between 700°C and 1200°C, even more preferably between 750°C and 1150°C.
[0052] The heat treatment according to the method of the invention makes it possible to obtain heat treated lithium zirconium phosphate having the desired properties, in particular the desired crystal structure.
[0053] The process of the present invention may comprise the further step of comminuting, preferably ball milling, the heat treated lithium zirconium phosphate.
[0054] Ball milling is preferably carried out with ZrO2 balls, for example about 0.5 mm in diameter, in a suitable solvent, such as ethanol or isopropanol.
[0055] Use of lithium zirconium phosphate in lithium-ion batteries
[0056] The present invention further provides the use of the lithium zirconium phosphate according to the invention in a lithium ion battery, in particular as a component of the solid electrolyte of a lithium ion battery, as an additive in a liquid or gel electrolyte or as a constituent of an electrode of a lithium ion battery.
[0057] The present invention further provides a lithium-ion battery comprising a lithium zirconium phosphate according to the invention or obtainable by the process of the invention.
[0058] Lithium ion batteries of the present invention can include an active positive electrode (cathode), a negative electrode, a separator, and an electrolyte that includes a compound that includes lithium.
[0059] The positive electrode (cathode) of a lithium ion battery typically includes a current collector and a positive electrode active material layer formed on the current collector.
[0060] The current collector may be an aluminum foil, a copper foil, a nickel foil, a stainless steel foil, a titanium foil, a polymer substrate coated with a conductive metal, or a combination thereof.
[0061] The active cathode material may include materials that can reversibly intercalate / deintercalate lithium ions, and are well known in the art. Such active cathode materials may include transition metal oxides, such as mixed oxides that include Ni, Co, Mn, V or other transition metals and optionally lithium. The mixed lithium transition metal oxides preferably used as active cathode materials are selected from the group consisting of lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, lithium nickel manganese oxide, lithium iron phosphate, lithium manganese oxide, or mixtures thereof.
[0062] The negative electrode of the lithium ion battery can include any suitable material commonly used in secondary lithium ion batteries that can reversibly intercalate / deintercalate lithium ions. Representative examples include carbonaceous materials including crystalline carbon such as plate-shaped, flake-shaped, spherical or fibrous natural or artificial graphite, amorphous carbon such as soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc., or mixtures thereof. In addition, lithium metal, lithium layer, or conversion material (e.g., Si or Sn) can be used as the negative electrode active material.
[0063] The present invention further provides an electrode, such as a positive or negative electrode for a lithium ion battery, comprising the lithium zirconium phosphate of the present invention. Specifically, the lithium zirconium phosphate of the present invention can be a dopant or coating material for the electrode.
[0064] The present invention further provides an electrolyte for a lithium ion battery comprising the lithium zirconium phosphate of the present invention.
[0065] The electrolyte in a lithium-ion battery can be in the form of a liquid, gel or solid.
[0066] The liquid electrolyte of a lithium ion battery may include any suitable organic solvent commonly used in lithium ion batteries, such as anhydrous ethylene carbonate (EC), dimethyl carbonate (DMC), propylene carbonate, methyl ethyl carbonate, diethyl carbonate, gamma butyrolactone, dimethoxyethane, fluoroethylene carbonate, vinyl ethylene carbonate, or mixtures thereof.
[0067] The gel electrolyte includes a gel polymer.
[0068] The solid electrolyte of a lithium-ion battery may include an oxide, such as a lithium metal oxide, a sulfide, a phosphate, or a solid polymer.
[0069] The liquid or polymer gel electrolyte of a lithium ion battery typically contains a lithium salt, such as lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), Li2SiF6, lithium triflate, LiN(SO2CF2CF3)2, lithium nitrate, lithium bisoxalate, lithium cyclodifluoromethane-1,1-bis(sulfonyl)imide, lithium cyclohexafluoropropane-1,1-bis(sulfonyl)imide, and mixtures thereof.
[0070] Lithium-ion batteries, especially those with a liquid or gel electrolyte, may also be equipped with a separator to prevent direct contact between the two electrodes, which could lead to an internal short circuit.
[0071] The material of the separator may include polyolefin resin, fluorinated polyolefin resin, polyester resin, polyacrylonitrile resin, cellulose resin, nonwoven fabric, or a mixture thereof. Preferably, the material includes polyolefin resin such as polyethylene or polypropylene based polymer, fluorinated resin such as polyvinylidene fluoride polymer or polytetrafluoroethylene, polyester resin such as polyethylene terephthalate and polybutylene terephthalate, polyacrylonitrile resin, cellulose resin, nonwoven fabric, or a mixture thereof.
[0072] The lithium ion battery according to the present invention may comprise a liquid electrolyte, a gel electrolyte or a solid electrolyte. A liquid mixture of a lithium salt and an organic solvent that is not cured, polymerized or crosslinked is called a "liquid electrolyte" in the context of the present invention. A gel or solid mixture comprising a cured, polymerized or crosslinked compound or mixtures thereof, optionally a solvent, and a lithium salt is called a "gel electrolyte". Such a gel electrolyte can be prepared by polymerization or crosslinking of a mixture comprising at least one reactive, i.e. polymerizable or crosslinkable, compound and a lithium salt.
[0073] A special type of lithium-ion battery is the lithium polymer battery, in which a polymer electrolyte is used instead of a liquid electrolyte. The electrolyte in similar solid-state batteries can also include other types of solid electrolytes, such as sulfide or oxide solid electrolytes, or mixtures thereof.
[0074] The batteries of the present invention can be lithium metal batteries, such as lithium air, lithium sulfur (Li-S), and other types of lithium metal batteries.
[0075] Li-air batteries typically contain a porous carbon positive electrode and an electrolyte of the organic, glass-ceramic or polymer-ceramic type. Li-sulfur (Li-S) batteries typically contain iron disulfide (FeS2), iron sulfide (FeS), copper sulfide (CuS), lead sulfide, and copper sulfide (PbS+CuS) negative electrodes.
[0076] For example, lithium-selenium (Li-Se), lithium-manganese dioxide (Li-MnO2 or Li / Al-MnO2), lithium-monofluoride (Li-(CF) x There are also many other known types of lithium metal batteries such as lithium ion battery (Li-I2), lithium ion battery (Li-I3), lithium ion battery (Li-I4), lithium ion battery (Li-I5), lithium ion battery (Li-I6), lithium ion battery (Li-I7), lithium ion battery (Li-I8), lithium ion battery (Li-I9), lithium ion battery (Li-I10), lithium ion battery (Li-I11), lithium ion battery (Li-I12), lithium ion battery (Li-I13), lithium ion battery (Li-I14), lithium ion battery (Li-I15), lithium ion battery (Li-I16), lithium ion battery (Li-I17), lithium ion battery (Li-I18), lithium ion battery (Li-I19), lithium ion battery (Li-I20), lithium ion battery (Li-I19), lithium ion battery (Li-I12), lithium ion battery (Li-I13), lithium ion battery (Li-I14), lithium ion battery (Li-I15), lithium ion battery (Li-I16), lithium ion battery (Li-I17), lithium ion battery (Li-I18), lithium ion battery (Li-I19 ... [Brief description of the drawings]
[0077] [Figure 1] 4 is a TEM image of lithium zirconium phosphate particles prepared as described in Comparative Example 1. [Diagram 2] 4 is a TEM image of lithium zirconium phosphate particles prepared as described in Comparative Example 2. [Diagram 3] 1 is a TEM image of lithium zirconium phosphate particles prepared as described in Example 1. [Figure 4] 1 shows XRD patterns of lithium zirconium phosphate prepared as described in Examples 1-2 and Comparative Examples 1-2. [Diagram 5] SEM images of NMC dry-coated with fumed lithium zirconium phosphate particles are shown (a - backscattered electron (BSE) image, b - EDX mapping of Zr, c - high-resolution SEM image). [Figure 6] FIG. 1 shows the rate and cycle performance of bare NMC and NMC dry-coated with fumed lithium zirconium phosphate particles in a lithium-ion battery with liquid electrolyte. [Figure 7]Figure 1 shows the charge and discharge curves in the initial cycle at a discharge current of 0.066 mA (0.035 C) for a sulfide-based all-solid-state battery with a solid electrolyte of Li6PS5Cl. [Figure 8] The charge and discharge curves of a sulfide-based all-solid-state battery with a solid electrolyte of Li6PS5Cl at the 4th cycle at a discharge current of 1.4 mA (0.75 C) are shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0078] (Example)
[0079] Comparative Example 1 6.34 kilograms of an aqueous solution containing 157.8 g of LiNO3 (metal content: 4% by weight), 1733 g of Zr(NO3)4 (metal content: 6% by weight) were prepared. 1190 grams of H3PO4 (85% by weight in water) were added dropwise to the solution of metal salts under vigorous stirring, forming a dispersion containing a white precipitate. The composition of the compound thus obtained corresponded to the formula LiZr2(PO4)3.
[0080] This dispersion is 1.5 kg / h and air is 15 Nm 3 The aerosol was generated through a two-component nozzle and sprayed into the tubular reactor using a combustion flame. The combustion gases of the flame were 14.3 Nm 3 / h hydrogen and 30Nm 3 / h of air. In addition, 25 Nm 3 / h secondary air was used. After the reactor the reaction gas was cooled and filtered.
[0081] The particle characteristics are shown in Table 1, TEM images of the particles are shown in Figure 1, and XRD analysis (Figure 4) showed that the main phase of the product was cubic zirconium phosphate.
[0082] Comparative Example 2 6.34 kilograms of an ethanol solution containing 157.8 g of LiNO3 (metal content: 4% by weight), 1733 g of Zr(NO3)4 (metal content: 6% by weight) were prepared. 1190 grams of H3PO4 (85% by weight in water) were added dropwise to the solution of metal salts under vigorous stirring, forming a dispersion containing a white precipitate. The composition of the compound thus obtained corresponded to the formula LiZr2(PO4)3. This dispersion is 1.5 kg / h and air is 15 Nm 3 The aerosol was generated through a two-component nozzle and sprayed into the tubular reactor using a combustion flame. The combustion gases of the flame were 8.4 Nm 3 / h hydrogen and 30Nm 3 / h of air. In addition, 25 Nm 3 / h secondary air was used. After the reactor the reaction gas was cooled and filtered. The particle characteristics are shown in Table 1, TEM images of the particles are shown in Figure 2, and XRD analysis (Figure 4) showed that the main phase of the product was cubic zirconium phosphate.
[0083] Comparative Example 3 61.4 grams of solution were prepared by mixing 2.9 grams of a commercial solution containing 2% by weight of lithium in the form of lithium neodecanoate dissolved in naphtha (Borchers® Deca Lithium 2) and 50 grams of a commercial solution containing 11.86% by weight of Zr in the form of zirconium ethylhexanoate dissolved in white spirit (Octa Solingen® Zirconium 12). 8.6 grams of H3PO4 (85% by weight in water) were added dropwise to the solution of metal salts under vigorous stirring. Phase separation was observed and it was not possible to spray the solution uniformly. No spraying experiments were performed.
[0084] Example 1 3370 g of a commercial solution containing 2% by weight of lithium in the form of lithium neodecanoate dissolved in naphtha (Borchers® Deca Lithium 2), 15 kg of a commercial solution containing 11.86% by weight of Zr in the form of zirconium ethylhexanoate dissolved in white spirit (Octa Solingen® Zirconium 12) and 5384 g of a commercial solution containing 16.83% by weight of phosphorus in the form of triethyl phosphate (Alfa Aesar) were mixed to obtain 23.75 kilograms of a clear solution, which corresponds to the composition LiZr2(PO4)3.
[0085] This dispersion is 1.5 kg / h and air is 15 Nm 3 The aerosol was generated through a two-component nozzle and sprayed into the tubular reactor using a combustion flame. The combustion gases of the flame were 8.5 Nm 3 / h hydrogen and 30Nm 3 / h of air. In addition, 25 Nm 3 / h secondary air was used. After the reactor the reaction gas was cooled and filtered.
[0086] The particle characteristics are shown in Table 1, TEM images of the particles are shown in Figure 3, and XRD analysis (Figure 4) showed that the major phase of the product was rhombohedral lithium zirconium phosphate.
[0087] Example 2 1056 g of a commercial solution containing 2 wt.% lithium in the form of lithium neodecanoate (Borchers® Deca Lithium 2) dissolved in naphtha, 2453 g of a commercial solution containing 18.01 wt.% Zr in the form of zirconium ethylhexanoate (Octa Solingen® Zirconium 12) dissolved in white spirit, and 1408 g of a commercial solution containing 16.83 wt.% phosphorus in the form of triethyl phosphate (Alfa Aesar) were mixed to obtain 6.18 kilograms of a clear solution. An additional solution containing 60.8 g of Ca(NO3)2×4H2O, 1200 g of ethanol, and 1200 g of ethylhexanoic acid was added with constant stirring until a clear solution was obtained. The solution was concentrated to 1.8 kg of Li 1.2 Ca 0.1 Zr 1.9 This corresponds to the composition of (PO4)3.
[0088] This dispersion is 1.5 kg / h and air is 15 Nm 3 The aerosol was generated through a two-component nozzle and sprayed into the tubular reactor using a combustion flame. The combustion gases of the flame were 8.7 Nm 3 / h hydrogen and 30Nm 3 / h of air. In addition, 25 Nm 3 / h secondary air was used. After the reactor the reaction gas was cooled and filtered.
[0089] The particle characteristics are shown in Table 1 and XRD analysis (Figure 4) showed that the major phase of the product was rhombohedral lithium zirconium phosphate.
[0090] The particle characteristics of the resulting products, summarized in Table 1, show that relatively high BET surface areas (17-44 m for the comparative examples) can be achieved by simply using the inventive combination of metal carboxylates and ethyl phosphate in a water-free solution. 2 / g vs 4.3~4.7m 2 The results show that the resulting lithium zirconium phosphate has a higher tamp density (approximately 100 g / L vs. approximately 300 g / L in the comparative example), a smaller particle size (76-130 nm vs. approximately 4 μm in the comparative example), and a lower tamping density (approximately 50 g / L vs. approximately 300 g / L in the comparative example).
[0091] [Table 1]
[0092] Analysis of lithium zirconium phosphate (LZP)-coated mixed lithium transition metal oxides by SEM-EDX
[0093] The NMC powder was mixed with the respective amount (1.0 wt%) of the fumed LZP powder from Example 1 in a high intensity laboratory mixer (SOMAKON mixer MP-GL with 0.5 L mixing unit) at 500 rpm for 1 min to homogenously mix the two powders, then the mixing intensity was increased to 2000 rpm for 5 min to achieve dry coating of the NMC particles with the LZP powder. The thickness of the LZP coating layer on the NMC particles was about 15-200 nm.
[0094] FIG. 5 shows a dry coating with LZP ((FIG. 5a, b, c) fumed LZP of Example 1). Figure 1 shows SEM images of NMC dry-coated with fumed LZP. Comparison of the backscattered electron image (a) and EDX mapping of Zr of NMC dry-coated with fumed LZP (b) reveals complete and uniform coverage of all cathode particles by the fumed LZP. No larger LZP agglomerates were detected, indicating good dispersion of the nanostructured fumed LZP particles was achieved. Furthermore, no free unbound LZP particles were found next to the cathode particles, indicating strong adhesion between the coating and the substrate. A high-resolution SEM image (c) shows uniform distribution of fumed LZP with high surface coverage of the CAM.
[0095] Electrochemical testing of lithium-ion batteries using liquid electrolytes
[0096] Electrodes for electrochemical measurements were prepared by blending 90 wt% NMC with 5 wt% PVDF (Solef PVDF 5130) as a binder and 5 wt% SUPER PLi (TIMCAL) as a conductive additive under an inert gas atmosphere. N-methyl-2-pyrrolidone (NMP) was used as the solvent. The slurry was cast on an aluminum foil and dried at 120 °C for 20 min on a heating plate in air. The electrode sheet was then dried at 120 °C for 2 h in a vacuum oven. Circular electrodes with a diameter of 12 mm were punched out, calendared at a pressure of 90 psi, and dried again at 120 °C for 12 h in a vacuum oven to remove residual water and NMP. For cycle testing, the cells were assembled as CR 2032 type coin cells (MTI Corporation) in an argon-filled glove box (GLOVEBOX SYSTEMTECHNIK GmbH). Lithium metal (ROCKWOOD LITHIUM GmbH) is used as the negative electrode material. The separator was Celgard 2500. 25 μL of a 1 M solution of LiPF6 in ethylene carbonate and ethyl methyl carbonate (50:50 wt / wt; Sigma-Aldrich) was used as the electrolyte. The cell was clamped with a crimper (MTI). For electrochemical evaluation, galvanostatic cycling was performed between 3.0 and 4.3 V. For the calculation of capacity and specific current, only the mass of active material was considered. For cycling coin-shaped half cells, the C-rate was increased from 0.1 / 0.1 (charge / discharge) to 0.3 / 0.3, 0.5 / 0.5, 1.0 / 1.0, 1.0 / 2.0 and 1.0 / 4.0 C every 4 cycles. Afterwards, the cells were cycled at 0.5 / 0.5 C for long-term stability testing.
[0097] Figure 6 shows the effect of LZP coating layer on cycle performance. The performance of NMC dry coated with fumed LZP of Example 1 is compared with that of uncoated NMC as a reference. From the graph shown, it can be easily recognized that dry coated fumed LZP coating significantly improves the stability and cycle life of NMC. NMC dry coated with fumed LZP shows higher discharge capacity over the full cycle, first rate test and long-term cycle test. It also shows higher initial specific discharge capacity at 0.1C than uncoated NMC.
[0098] Electrochemical testing of lithium-ion batteries using sulfide-based all-solid-state batteries
[0099] The powder composite electrode is prepared by mixing the active material NCM (AM), conductive carbon-doped carbon nanofiber (CNF), and solid electrolyte (Li6PS5Cl, SE) in a mass ratio of 63:2:35 in an agate mortar for 30 min. To produce a free-standing flexible dry film, the above prepared powder electrode is mixed in an agate mortar at 100 °C with 0.3 wt% polytetrafluoroethylene (PTFE, emulsion-polymerized fine powder; particle size 300-700 μm; softening point 320-330 °C; molecular weight 10 7 ~10 8 g / mol).
[0100] After 1 min of mixing and shearing, a single flake was formed. The flake was placed on a hot plate and rolled to the desired thickness (approximately 100 μm). Each sample was prepared at least twice to ensure the reproducibility of the process. To make free-standing electrolyte films, the solid electrolyte was mixed with 0.15 wt% PTFE and processed similarly to the negative electrode films.
[0101] Test cells were fabricated to measure the basic properties of the positive electrode composite, such as the charge / discharge potential profile and rated discharge capacity.
[0102] The cells were fabricated using a 13 mm diameter die. The test cells consisted of a stainless steel outer casing with Teflon insulation. In a typical cell, the electrolyte Li6PS5Cl powder was spread evenly inside the die by a micro spatula. The powder was then compressed into a pellet by pressing once. The cathode composite powder was evenly distributed across the compressed electrolyte surface in the die. The anode layer was then compressed. On the opposite side of the cell stack, the lithium-indium alloy anode was placed and compressed. All cell components were again pressed together and fully pelletized by using a hydraulic press (4 tons applied for 30 seconds): 300 MPa.
[0103] After compression, the cell stack was placed inside the outer steel casing and electrical contact within the cell was maintained by screws, which were tightened with a pre-set torque of 3.0 Nm.
[0104] All the above processes were carried out in an Ar-filled glove box (<0.1 ppm of H2O and O2).
[0105] The cycle and rate performance of the cells were measured by a battery tester CTS-Lab (BaSyTec, Germany). The standard rate performance test plan consisted of three different discharge currents ranging from 0.066mA (0.035C) to 1.4mA (0.75C) while keeping the charge rate constant at 0.14mA (0.075C) including CV steps. The standard cut-off voltages for the cycle tests were 3.63V for charge and 1.93V for discharge.
[0106] Figure 7 shows the effect of the LZP coating layer on the rate performance at a discharge current of 0.066 mA (0.035 C) at the first cycle with different coating amounts of LZP of 0.5, 1, and 2 wt%. The discharge capacity at 0.066 mA of the NMC dry-coated with fumed LZP of Example 1 is compared with the performance of the uncoated NMC as a reference. From the graph shown, it can be easily recognized that no significant improvement was observed in the initial discharge capacity at a discharge rate as low as 0.035 C in the sulfide-based solid-state battery.
[0107] FIG. 8 shows the effect of the LZP coating layer on the rate performance at a discharge current of 1.4 mA (0.75C) at the fourth cycle with different coating amounts of LZP of 0.5, 1 and 2 wt%. The discharge capacity at 0.75C of the NMC dry-coated with fumed LZP of Example 1 is compared with the performance of the uncoated NMC as a reference. From the graph shown, it can be easily recognized that the dry-coated fumed LZP coating significantly improves the discharge rate performance of the NMC. The NMC dry-coated with fumed LZP shows higher discharge capacity at high discharge rates such as 0.75C in sulfide-based solid-state batteries.
Claims
1. General formula Li a Zr b M c (P.O. 4 ) d where M is at least one metal different from Li and Zr; 0.5≦a≦5.0, 0.5≦b≦5.0, 0≦c≦5, and 1≦d≦5; The lithium zirconium phosphate is in the form of aggregated primary particles, 5m 2 / g to 100m 2 / g BET surface area, Determined by static light scattering (SLS), 50 = numerical average particle size between 0.03 μm and 2 μm, and Characterized in that it has a tamping density of 20 g / L to 200 g / L; Lithium zirconium phosphate.
2. A method for producing the lithium zirconium phosphate according to claim 1, comprising the steps of: by flame spray pyrolysis, At least one solution of a metal precursor, lithium and zirconium carboxylates, each of which metal carboxylates contain from 5 to 20 carbon atoms; Organophosphates, A solvent containing less than 10% by weight of water; The solution comprising the compound is subjected to flame spray pyrolysis. method.
3. Spray flame pyrolysis, a) atomizing the solution of said metal precursor to obtain an aerosol by means of an atomizer gas; b) reacting the aerosol with a flame obtained by igniting a mixture of a fuel gas and an oxygen-containing gas in a reaction space of a reactor to obtain a reaction flow; c) cooling the reaction stream d) then removing solid lithium zirconium phosphate from said reaction stream. Characterized in that it comprises The method of claim 2.
4. the lithium carboxylate and the zirconium carboxylate are, independently of one another, linear, branched or cyclic pentanoate (C5), hexanoate (C6), heptanoate (C7), octanoate (C8), nonanoate (C9), decanoate (D10), undecanoate (C11), dodecanoate (C12), tridecanoate (C13), tetradecanoate (C14), pentadecanoate (C15), hexadecanoate (C16), heptadecanoate (C17), octadecanoate (C18), nonadecanoate (C19), icosanoate (C20) carboxylates, and mixtures thereof; Characterized in that The method according to claim 2 or 3.
5. The organic phosphate is phosphonic acid (H 3 P.O. 3 ), orthophosphoric acid (H 3 P.O. 4 ), metaphosphoric acid (HPO 3 ), pyrophosphate (H 4 P 2 O 7 ), polyphosphoric acid, and mixtures thereof; Characterized in that The method according to claims 2 to 4.
6. the organophosphate salt is selected from alkyl esters, aryl esters, mixed alkyl / aryl esters, and mixtures thereof; Characterized in that The method according to claims 2 to 5.
7. The organic phosphate is an alkyl ester having an alkyl group having 1 to 10 carbon atoms. Characterized in that The method according to claims 2 to 6.
8. The solvent is selected from the group consisting of linear or cyclic, saturated or unsaturated, aliphatic or aromatic hydrocarbons, esters of carboxylic acids, ethers, alcohols, carboxylic acids, and mixtures thereof; Characterized in that The method according to claims 2 to 7.
9. the solution of metal precursors comprises a chelating agent selected from the group consisting of diamines and 1,3-dicarbonyl compounds; Characterized in that The method according to claims 2 to 8.
10. The method further comprises the step of heat treating the lithium zirconium phosphate produced by flame spray pyrolysis at a temperature of 600° C. to 1300° C. The method according to claims 2 to 9.
11. further comprising grinding the heat treated lithium zirconium phosphate. The method of claim 10.
12. 2. Use of the lithium zirconium phosphate according to claim 1 as a component of a solid electrolyte, as an additive in a liquid or as a gel electrolyte or as a constituent of an electrode in a lithium ion battery.
13. 10. An electrode for a lithium ion battery comprising the lithium zirconium phosphate of claim 1.
14. 10. An electrolyte for a lithium ion battery comprising the lithium zirconium phosphate of claim 1.
15. A lithium ion battery comprising the lithium zirconium phosphate of claim 1.
16. 16. The lithium ion battery of claim 15 comprising a liquid or gel electrolyte.
17. 16. The lithium ion battery of claim 15 which is a solid-state battery.
Citation Information
Patent Citations
Metal feeding system for nanoparticle production
JP2006525930A
Olivine, a multi-functional alloy for lithium-ion batteries
JP2011517361A
Nasicon-type oxide particle for lithium ion secondary battery solid electrolyte and method for producing the same
JP2020102371A
Flame spray pyrolysis method for forming nanoscale lithium metal phosphate powders
US20140084503A1
Microparticle mixture, positive electrode active material, positive electrode, secondary cell, and method for producing same
WO2012105637A1